NiCrW alloy-based composite material for high-temperature alloy movement matching pair as well as preparation method and application of NiCrW alloy-based composite material

By doping bismuth oxide (Bi2O3) into the NiCrW alloy matrix, a NiCrW alloy base composite material for sports matching with high-temperature alloy was prepared, which solved the problems of lubrication and wear resistance in high-temperature oxidation environment, and achieved low friction and wear resistance in a wide temperature range. It is suitable for components such as aero engine turbine rotating mechanism and self-lubricating bearings.

CN119506662APending Publication Date: 2025-02-25LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702977.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide effective lubrication and wear-resistant materials for aircraft engine turbine rotating mechanisms and self-lubricating bearing components in high-temperature oxidation environments, especially lacking systematic research in the design of high-temperature self-lubricating functionalities and tribological properties of NiCrW-based self-lubricating composites.

Method used

NiCrW alloy is used as the matrix and doped with oxide ceramic phase bismuth oxide (Bi2O3) with extremely small interaction parameters. NiCrW alloy-based composite materials for high-temperature alloy motion matching pairs are prepared through mechanical alloying, pressing and hot pressing sintering.

Benefits of technology

It achieves low friction and wear resistance in a wide temperature range of 600℃ to 1000℃, with a friction coefficient below 0.35 and a wear rate within 10~14m3/Nm, which solves the problem of lubrication and wear of aircraft engine turbine rotating mechanism and self-lubricating bearing components at high temperatures, ensuring the safe and reliable operation of related equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506662A_ABST
    Figure CN119506662A_ABST
Patent Text Reader

Abstract

The invention provides a NiCrW alloy-based composite material for a high-temperature alloy movement matching pair as well as a preparation method and application of the NiCrW alloy-based composite material, and belongs to the technical field of self-lubricating composite materials. According to the invention, oxide ceramic phase bismuth oxide (Bi2O3) is doped in a NiCrW alloy matrix with good mechanical property and high temperature resistance. In the hot pressed sintering process, Bi2O3 is decomposed at high temperature and reacts with Ni and Cr to generate NiBi and Cr2O3 new phases, the friction surface of the composite material is subjected to a friction chemical reaction in the high-temperature friction and wear stage, Bi2O3 is regenerated, and the Bi2O3 and NiO and Cr2O3 lubricating and wear-resistant phases in the composite material form a synergistic lubricating and wear-resistant effect, so that the composite material has excellent high-temperature friction and wear performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of self-lubricating composite materials, and in particular to a NiCrW alloy-based composite material for high-temperature alloy moving parts, and a preparation method and application thereof. Background Art

[0002] With the rapid development of aviation, aerospace and thermonuclear industries, many core mechanical components (such as rolling bearings, air foil bearings, gears, cylinder walls and piston rings) need to have good mechanical and tribological properties at high temperatures, so as to achieve high performance, high efficiency and high durability of mechanical systems. In order to solve the lubrication and wear problems of the self-lubricating bearings of the turbine rotating mechanism of aircraft engines and the directional solidification high-temperature alloy shaft (such as IC10) during relative motion in a high-temperature oxidizing environment, it is necessary to develop new self-lubricating bearing materials with low friction and wear resistance under corresponding working conditions. Nickel-chromium-tungsten alloy has the advantages of high lasting strength, good oxidation resistance, corrosion resistance and high-temperature wear resistance, and has a good prospect of being widely used in high-temperature structural parts in the fields of aviation and aerospace. Therefore, taking NiCrW ternary alloy as the matrix and using solid lubrication technology to develop NiCrW alloy-based high-temperature low-friction and wear-resistant composite materials with continuous lubrication function is a metal-based high-temperature self-lubricating wear-resistant material and high-temperature self-lubricating alloy with important engineering application value.

[0003] At present, a large number of papers and patents have reported various nickel-based high-temperature lubricating materials, but there are few systematic studies on the high-temperature self-lubricating function design and tribological properties of NiCrW-based self-lubricating composite materials. In particular, material tribological research and performance evaluation are closely related to mechanical friction pairs and related test conditions. As the key friction pair of the turbine rotating mechanism (IC10 high-temperature alloy and self-lubricating metal-ceramic composite material), there are few reports on the tribological behavior of relative motion in a high-temperature oxidizing environment. Moreover, the friction and wear tests in the literature and related patents basically use ceramic balls (such as Al 2 O 3 、Si 3 N 4 ) or ordinary alloy steel (such as GCr15) as friction pair materials, while most of the thermomechanical material pairs in practical applications are new generation high temperature alloys, so it is difficult for related research to reflect its specific practicality and reliability. Summary of the invention

[0004] The purpose of the present invention is to provide a NiCrW alloy-based composite material for high-temperature alloy kinematic pairs and a preparation method and application thereof. The composite material has good high-temperature, low-friction and wear resistance and can be used as a high-temperature alloy shaft kinematic pair material for a turbine rotating mechanism of an aero-engine to achieve practicality and reliability.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a NiCrW alloy-based composite material for high-temperature alloy moving parts, comprising the following raw materials in percentage by mass:

[0007] Ni 66.50~69.30%, Cr 19.0~19.80%, W 9.50~9.90%, Bi 2 O 3 1.0~5.0%.

[0008] Preferably, Ni 67-68.25%, Cr 19.2-19.6%, W 9.60-9.80%, Bi 2 O 3 2~4%.

[0009] The present invention provides a method for preparing the NiCrW alloy-based composite material for high-temperature alloy moving parts described in the above technical solution, comprising the following steps:

[0010] According to the composition ratio of the NiCrW alloy-based composite material for high-temperature alloy motion pair, Ni powder, Cr powder, W powder and Bi 2 O 3 mixing, and performing mechanical alloying to obtain mixed powder;

[0011] The mixed powder is pressed and hot-pressed and sintered in sequence to obtain a NiCrW alloy-based composite material for high-temperature alloy moving parts.

[0012] Preferably, the Ni powder, Cr powder, W powder and Bi 2 O 3 The particle size is independently ≤100μm and the purity is independently >99.0%.

[0013] Preferably, the mechanical alloying method is wet ball milling; the wet ball milling time is 20 to 30 hours, the rotation speed is 200 to 400 r / min, and the ball-to-material mass ratio is 5 to 10:1.

[0014] Preferably, the pressing pressure is ≤10 MPa.

[0015] Preferably, the dynamic vacuum degree of the hot pressing sintering is less than 1.0×10 -2 Pa.

[0016] Preferably, the hot pressing sintering temperature is 1150-1250° C., the pressure is 25-30 MPa, and the heat and pressure holding time is 30-90 min.

[0017] The present invention provides the application of the NiCrW alloy-based composite material for high-temperature alloy moving parts described in the above technical solution or the NiCrW alloy-based composite material for high-temperature alloy moving parts prepared by the preparation method described in the above technical solution in aircraft engine turbine rotating mechanisms and self-lubricating bearing components.

[0018] The NiCrW alloy-based composite material for high-temperature alloy moving parts of the present invention has the following advantages:

[0019] The present invention dopes bismuth oxide (BiO) with a very small interaction parameter (0.008) into a NiCrW alloy matrix having good mechanical and high temperature resistance properties. 2 O 3 ). During the hot pressing sintering process, Bi 2 O 3 Decompose at high temperature and react with Ni and Cr to form NiBi and Cr 2 O 3 During the high temperature friction and wear stage, the friction chemical reaction on the friction surface of the composite material regenerates Bi 2 O 3 , and NiO, Cr in the composite material 2 O 3 The equal lubricating and anti-wear phases form a synergistic lubricating and anti-wear effect, which makes the composite material have excellent high-temperature friction and wear properties.

[0020] The composite material of the present invention has simple components, simple and conventional preparation process and low cost, has good low friction and wear resistance in the temperature range of room temperature (RT) to 1000°C, and with the increase of temperature, the friction coefficient and wear rate show a decreasing trend. In the wide temperature range of 600°C to 1000°C, the friction coefficient is below 0.35, and the wear rate is also within 10 ~ 14 m 3 / Nm order of magnitude, which solves the lubrication and wear "bottleneck" problem of aircraft engine turbine rotating mechanism and self-lubricating bearing components during low-temperature startup and high-temperature operation, and ensures the safe, stable and reliable operation of related equipment.

[0021] The compressive strength of the composite material of the present invention is greater than 1050MPa at room temperature, greater than 495MPa at 400°C, and greater than 277MPa at 800°C. It is rated as above level 2 anti-oxidation level in a 1000°C high-temperature anti-oxidation test, and its friction and wear performance is more stable and reliable during long-term use. It has low friction and wear resistance characteristics when worn against new generation high-temperature alloys such as IC10\DZ125L\K447A in a wide temperature range (RT-1000°C). It is suitable for parts and components serving under high temperature conditions such as turbine rotating mechanisms and self-lubricating bearings of aircraft engines working in high-temperature oxidation environments, achieving high-temperature lubrication and wear resistance. It can also be used to solve the lubrication and wear resistance problems between related sliding parts under extremely harsh working conditions such as wide temperature range, special media and high speed that are common in high-tech industries such as modern aviation, aerospace, nuclear technology and electricity.

[0022] The present invention uses IC10 high-temperature alloy as a dual material, tests the friction and wear properties of the composite material, simulates the actual application process of related thermal machinery, and realizes the key of low friction and wear resistance of the composite material in a wide temperature range during actual application, thereby achieving practicality and reliability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a friction coefficient curve of the material prepared in Example 1 of the present invention;

[0024] Figure 2 A histogram of the wear rate of the material prepared in Example 1 of the present invention;

[0025] Figure 3 This is a friction coefficient curve of the material prepared in Example 2 of the present invention;

[0026] Figure 4 A histogram of the wear rate of the material prepared in Example 2 of the present invention;

[0027] Figure 5 This is a friction coefficient curve of the material prepared in Example 3 of the present invention;

[0028] Figure 6 A histogram of the wear rate of the material prepared in Example 3 of the present invention;

[0029] Figure 7 This is a friction coefficient curve of the material prepared in Comparative Example 1 of the present invention;

[0030] Figure 8 A histogram of the wear rate of the material prepared in Comparative Example 1 of the present invention;

[0031] Fig. 9 XRD spectra of the ball-milled powders prepared in Examples 1 to 3 and Comparative Example 1;

[0032] Fig.10 XRD spectra of the hot-pressed sintered composite materials prepared in Examples 1 to 3 and Comparative Example 1;

[0033] Fig.11 SEM images and EDS distribution diagrams of the composite materials prepared in Examples 1 to 3 and Comparative Example 1 ((a). NCW, (b). NCW1B, (c). NCW2.5B, (d). NCW5B). DETAILED DESCRIPTION

[0034] In the present invention, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0035] The present invention provides a NiCrW alloy-based composite material for high-temperature alloy moving parts, comprising the following raw materials in percentage by mass:

[0036] Ni 66.50~69.30%, Cr 19.0~19.80%, W 9.50~9.90%, Bi 2 O 3 1.0~5.0%.

[0037] In the present invention, the mass percentage of Ni is more preferably 67-68.25%, more preferably 67.5-68%, the mass percentage of Cr is more preferably 19.2-19.6%, more preferably 19.3-19.5%, the mass percentage of W is more preferably 9.60-9.80%, more preferably 9.65-9.75%, and the mass percentage of Bi is more preferably 19.2-19.6%, more preferably 19.3-19.5%. 2 O 3 The mass percentage is more preferably 2 to 4%, and further preferably 2.5 to 3.0%.

[0038] According to the crystal ion polarizability theory proposed by Dimitrov, when the oxide has a lower interaction parameter, the number of surface vacancies will be higher, and it will have higher ion freedom and mobility. Especially under high temperature friction conditions, the significant ion mobility makes it show a low friction coefficient. The present invention uses Bi with a very small interaction parameter (0.008) 2 O 3 By doping NiCrW alloy, the composite material has good lubrication and anti-wear properties at high temperature.

[0039] The present invention provides a method for preparing the NiCrW alloy-based composite material for high-temperature alloy moving parts described in the above technical solution, comprising the following steps:

[0040] According to the composition ratio of the NiCrW alloy-based composite material for high-temperature alloy motion pair, Ni powder, Cr powder, W powder and Bi2 O 3 mixing, and performing mechanical alloying to obtain mixed powder;

[0041] The mixed powder is pressed and hot-pressed and sintered in sequence to obtain a NiCrW alloy-based composite material for high-temperature alloy moving parts.

[0042] In the present invention, the Ni powder, Cr powder, W powder and Bi 2 O 3 The particle size is preferably independently ≤100 μm and the purity is independently >99.0%.

[0043] In the present invention, the mechanical alloying method is wet ball milling; the wet ball milling time is preferably 20 to 30 hours, more preferably 20 hours, the rotation speed is preferably 200 to 400 r / min, more preferably 250 r / min, and the ball-to-material mass ratio is preferably 5 to 10:1, more preferably 10:1. The solvent used in the wet ball milling is preferably methanol; the present invention has no special limitation on the amount of the solvent, and it can be adjusted according to actual needs to ensure that the ball milling is completed.

[0044] The present invention preferably uses a planetary high-energy ball mill for wet ball milling, grinding for 30 minutes and stopping for 30 minutes. After the ball milling is completed, the obtained mixed material is dried and sieved out to obtain a mixed powder.

[0045] The present invention preferably places the mixed powder into a graphite mold, pre-coates the mold with h-BN (hexagonal boron nitride) for demoulding, presses it with a manual hydraulic press, and then places it in a ZT45-20Y vacuum hot pressing sintering furnace (Shanghai Chenhua) for hot pressing sintering.

[0046] In the present invention, the pressing pressure is preferably ≤10 MPa; the dynamic vacuum degree of the hot pressing sintering is <1.0×10 -2 Pa; the hot pressing sintering temperature is preferably 1150-1250°C, more preferably 1200°C, the pressure is preferably 25-30MPa, and the heat preservation and pressure holding time is preferably 30-90min, more preferably 60min.

[0047] After the hot pressing sintering is completed, the present invention preferably cools naturally along with the furnace to obtain a NiCrW alloy-based composite material for high-temperature alloy moving parts.

[0048] The present invention provides the application of the NiCrW alloy-based composite material for high-temperature alloy motion pairs described in the above technical solution or the NiCrW alloy-based composite material for high-temperature alloy motion pairs prepared by the preparation method described in the above technical solution in the turbine rotating mechanism and self-lubricating bearing parts of aircraft engines. The composite material of the present invention is mainly used for key friction pairs in turbine rotating mechanisms, specifically, friction pairs between IC10 high-temperature alloy shafts and bearings composed of the composite material of the present invention.

[0049] During the friction process, especially at high temperatures, the wear interface is not only subjected to stresses related to friction and contact forces, but also to thermal softening and oxidation, which may significantly change the overall wear performance. In order to obtain better tribological properties, the reaction products with good lubrication properties formed by temperature induction and tribochemistry can effectively absorb the friction interface energy while overcoming the friction interface adhesion, thereby forming a strong self-lubricating friction layer in situ and avoiding the vicious cycle of material performance degradation and material wear caused by friction reaction.

[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0051] In the following examples, Ni powder, Cr powder, W powder, Bi 2 O 3 The particle size of the powder is ≤100μm and the purity is >99.0%.

[0052] Example 1

[0053] The components and their mass percentages of the NiCrW alloy-based composite material for high-temperature alloy moving parts provided in this embodiment are as follows: Ni: 69.30%, Cr: 19.80%, W: 9.90%, Bi: 2 O 3 : 1%.

[0054] Ni powder, Cr powder, W powder, Bi powder with purity greater than 99.0% 2 O 3 Powder Ni: 69.30%, Cr: 19.80%, W: 9.90%, Bi 2 O 3 :1% mass ratio was mixed with 10 mL of methanol, and the resulting mixture was ball-milled in a planetary high-energy ball mill (FRITSCH, Germany) using a wet ball milling process, with a rotation speed of 250 r / min, a ball-to-material ratio of 10:1, and the grinding time was 30 min and rest time of 30 min, with a total ball-milling time of 20 h. After the grinding was completed, the powder was dried and sieved to obtain a ball-milled powder;

[0055] The mixed powder was weighed and placed in a graphite mold. The mold was pre-coated with h-BN and pre-pressed with a manual hydraulic press at a pressure of ≤10 MPa. The mold was placed in a ZT45-20Y vacuum hot pressing sintering furnace (Shanghai Chenhua) at a temperature of ≤1.0×10 -2 Pa under dynamic vacuum, the hot pressing sintering temperature is 1200℃, the applied pressure is 25MPa, the heat preservation and pressure holding time is 60min, and the furnace is naturally cooled to obtain a NiCrW alloy-based composite material for high-temperature alloy moving parts, which is recorded as NCW1B.

[0056] Example 2

[0057] The components and their mass percentages of the NiCrW alloy-based composite material for high-temperature alloy kinematic parts provided in this embodiment are as follows: Ni: 68.25%, Cr: 19.5%, W: 9.75%, Bi: 1. 2 O 3 : 2.5%.

[0058] Ni powder, Cr powder, W powder, Bi powder with purity greater than 99.0% 2 O 3 Powder Ni: 68.25%, Cr: 19.5%, W: 9.75%, Bi 2 O 3 : 2.5% mass ratio was mixed with 10 mL methanol, and the resulting mixture was ball-milled in a planetary high-energy ball mill (FRITSCH, Germany) by wet ball milling process, with a rotation speed of 250 r / min, a ball-to-material ratio of 10:1, grinding for 30 min, stopping for 30 min, and a total ball-milling time of 20 h. After the ball-milling was completed, it was dried and sieved to obtain ball-milled powder;

[0059] The mixed powder was weighed and placed in a graphite mold. The mold was pre-coated with h-BN and pre-pressed with a manual hydraulic press at a pressure of ≤10 MPa. The mold was placed in a ZT45-20Y vacuum hot pressing sintering furnace (Shanghai Chenhua) at a temperature of ≤1.0×10 -2 The hot pressing sintering was carried out under a dynamic vacuum degree of Pa, the hot pressing sintering temperature was 1200°C, the applied pressure was 30MPa, the heat preservation and pressure holding time was 60min, and the furnace was naturally cooled to obtain a NiCrW alloy-based composite material for high-temperature alloy moving parts, which was recorded as NCW2.5B.

[0060] Example 3

[0061] The components and their mass percentages of the NiCrW alloy-based composite material for high-temperature alloy moving parts provided in this embodiment are as follows: Ni: 66.50%, Cr: 19.00%, W: 9.50%, Bi: 2 O 3 : 5%.

[0062] Ni powder, Cr powder, W powder, Bi powder with purity greater than 99.0% 2 O 3 Powder Ni: 66.50%, Cr: 19.00%, W: 9.50%, Bi 2 O 3 :5% mass ratio was mixed with 10 mL methanol, and the resulting mixture was ball-milled in a planetary high-energy ball mill (FRITSCH, Germany) by wet ball milling process, with a rotation speed of 250 r / min, a ball-to-material ratio of 10:1, grinding for 30 min, stopping for 30 min, and a total ball-milling time of 20 h. After the ball-milling was completed, it was dried and sieved to obtain ball-milled powder;

[0063] The mixed powder was weighed and placed in a graphite mold. The mold was pre-coated with h-BN and pre-pressed with a manual hydraulic press at a pressure of ≤10 MPa. The mold was placed in a ZT45-20Y vacuum hot pressing sintering furnace (Shanghai Chenhua) at a temperature of ≤1.0×10 -2 The hot pressing sintering was carried out under a dynamic vacuum degree of Pa, the hot pressing sintering temperature was 1200°C, the applied pressure was 30MPa, the heat preservation and pressure holding time was 60min, and the furnace was naturally cooled to obtain a NiCrW alloy-based composite material for high-temperature alloy moving parts, which was recorded as NCW5B.

[0064] Comparative Example 1

[0065] The components and their mass percentages of the NiCrW alloy material provided in this comparative example are: Ni: 70%, Cr: 20%, and W: 10%.

[0066] Ni powder, Cr powder, W powder, Bi powder with purity greater than 99.0% 2 O 3 The powder was mixed with 10 mL of methanol in a mass ratio of Ni: 70%, Cr: 20%, and W: 10%. The obtained mixture was ball-milled in a planetary high-energy ball mill (FRITSCH, Germany) using a wet ball milling process at a speed of 250 r / min, a ball-to-material ratio of 10:1, and the grinding time was 30 min and the rest time was 30 min. The total ball-milling time was 20 h. After the ball-milling was completed, the mixed powder was dried and sieved to obtain a mixed powder.

[0067] The mixed powder was weighed and placed in a graphite mold. The mold was pre-coated with h-BN and pre-pressed with a manual hydraulic press at a pressure of ≤10 MPa. The mold was placed in a ZT45-20Y vacuum hot pressing sintering furnace (Shanghai Chenhua) at a temperature of ≤1.0×10 -2 The hot pressing sintering was carried out under a dynamic vacuum degree of Pa, the hot pressing sintering temperature was 1200°C, the applied pressure was 25 MPa, the heat preservation and pressure holding time was 60 min, and the furnace was naturally cooled to obtain a NiCrW alloy material, which was recorded as NCW.

[0068] Performance Testing

[0069] 1) GB / T 228.1-2015 "Tensile Test for Metallic Materials Part 2: Room Temperature Test Method" was used to examine the room temperature tensile strength of the composite material, and GB / T 228.2-2015 "Tensile Test for Metallic Materials Part 2: High Temperature Test Method" was used to examine the high temperature tensile strength of the composite material; GB / T7314-2005 "Room Temperature Compression Test Method for Metallic Materials" was used to examine the room temperature compressive strength of the composite material; HB 7571-1997 "Metal High Temperature Compression Test Method" was used to examine the high temperature compressive strength of the composite material; ASTM G99-23 "Standard Test Method for Wear and Friction Tests with Pin-Disc or Ball-Disc Apparatus" was used to test the friction and wear performance; HB5258-2000 "Test Method for Determination of Oxidation Resistance of Steel and High Temperature Alloys" was used to test the oxidation resistance level;

[0070] The results show that the compressive strength of the composite material prepared in Example 1 is 1057.59±22.98MPa at room temperature, 495.43±44.96MPa at 400°C, and 277.75±4.53MPa at 800°C. It is rated as Grade 2 in the 1000°C high temperature oxidation resistance test.

[0071] The compressive strength of the composite material prepared in Example 2 is 901.03±10.86MPa at room temperature, 362.87±4.48MPa at 400°C, and 211.47±12.66MPa at 800°C. It is rated as Grade 2 in the 1000°C high temperature oxidation resistance test.

[0072] The compressive strength of the composite material of Example 3 at room temperature is 914.68±2.58 MPa, the compressive strength at 400°C is 397.63±41.29 MPa, and the compressive strength at 800°C is 234.45±5.09 MPa. In the 1000°C high temperature oxidation resistance test, it is rated as Grade 2 oxidation resistance.

[0073] The compressive strength of the NiCrW alloy material prepared in Comparative Example 1 is 2078.06±9.68MPa at room temperature. At 400 and 800°C, the NCW alloy has high ductility under the action of temperature. During the compression test, the sample did not break as the stress continued to increase, but was flattened into a "drum shape" with an increasing cross-sectional area, but it was almost impossible to break. This material is generally referred to as a ductile material, and it can usually be considered that ductile materials do not have a compressive strength limit. In the 1000°C high-temperature oxidation resistance test, it was rated as a weak oxidation resistance level 4. Although the mechanical strength of the pure alloy in Comparative Example 1 is relatively high, its high-temperature oxidation resistance and friction and wear resistance are relatively poor (see Figures 7-8) and severe high-temperature adhesive wear (the sample softens and adheres very severely at a high temperature of 1000°C, and the bolt and disk are stuck and the friction test cannot be completed), which is not conducive to application in high-temperature oxidative wear environments.

[0074] 2) The composite materials prepared in Examples 1 to 3 and Comparative Example 1 were tested for friction and wear properties in a high temperature friction tester (UMT-3, Bruker, USA) (10N, 10m / min, 1h, atmospheric environment, rotary bolt hemispherical surface-to-surface contact, Φ5mm×10mm IC10 high temperature alloy bolt (a wear bolt made of IC10 high temperature alloy, r=5mm hemispherical head), Φ24mm×8mm composite material dual disk, taking the average value of three times). The friction and wear properties are shown in Figures 1 to 8 .

[0075] Depend on Figures 1 to 8 It can be seen that the materials prepared in Examples 1 to 3 ( Figures 1 to 6 ) and the material in Comparative Example 1 ( Figures 7-8 ) compared to a small amount of Bi 2 O 3 The addition has a favorable effect on the friction coefficient of the composite at high temperature and the wear rate at room temperature, but Bi 2 O 3 Excessive addition of Bi has a certain adverse effect on the wear rate of composite materials at medium and high temperatures. However, its impact is within a controllable range. 2 O 3 With the addition of, the composite materials have good friction and wear properties at a high temperature of 1000°C, and their high temperature oxidation resistance is level 2, meeting the performance requirements for application in a high temperature oxidation and wear environment.

[0076] 3) Fig. 9 XRD spectra of the ball-milled powders prepared in Examples 1 to 3 and Comparative Example 1; Fig.10 XRD spectra of the hot-pressed sintered composite materials prepared in Examples 1 to 3 and Comparative Example 1;

[0077] Depend on Fig. 9 It can be seen that after high-energy ball milling for 20 hours, the XRD spectra of the four composite powders mainly contain Ni, Cr, W) and Bi 2 O 3 This indicates that the composition of the composite material has not changed after ball milling. However, due to the low content of bismuth oxide added, Bi 2 O 3 The diffraction peak intensity is low. Fig.10 It can be seen that after vacuum hot pressing sintering, the XRD spectrum of the composite surface is mainly composed of Ni(Cr, W) solid solution and Cr 2 O 3In addition, after sintering, no Bi 2 O 3 The existence of diffraction peaks, but the diffraction peaks of NiBi appear. 2 O 3 As the addition content increases, it can be found that NiBi 3 The diffraction peak intensity gradually increases, which means that Bi 2 O 3 Decomposition occurs during the sintering process and reacts with other elements in the matrix to generate new phases. Therefore, it is speculated that the following reactions occur during the sintering process:

[0078] Bi 2 O 3 +2Cr→Cr 2 O 3 +2Bi (1.1)

[0079] Ni+Bi→NiBi (1.2)

[0080] Ni+3Bi→NiBi 3 (1.3)

[0081] Fig.11 The SEM images and EDS distribution diagrams of the composite materials prepared in Examples 1 to 3 and Comparative Example 1 ((a). NCW, (b). NCW1B, (c). NCW2.5B, (d). NCW5B). Fig.11 As shown in (a), the surface of NC W is mainly composed of light gray phase, and there are many evenly distributed black dot phases and dark gray block phases. By scanning the surface at low magnification, it is found that the black area is mainly composed of Cr and O elements, while the dark gray block area is mainly enriched in Cr elements, and the light gray area is mainly composed of Ni, Cr and W elements. Fig.10 From the XRD diffraction pattern, it is inferred that the black phase in the NCW composite material is mainly composed of Cr 2 O 3 The dark gray block phase is mainly a solid solution rich in Cr, while the light gray phase is a NiCrW solid solution. Fig.11 In (b~d), we can see that when Bi is added 2 O 3 After addition, the phases on the surface of the composite material changed significantly. At the same scale, the dark gray block phase in the composite material decreased, the light gray phase increased, and more and more white phases appeared near the black dot phase and the dark gray block phase. Especially for NCW5B, there is a white phase near almost every black phase and dark gray phase. The EDS surface scan results show that the addition of Bi 2 O 3The elemental composition of the composite material phase is similar to that of NCW. The black area is mainly composed of Cr and O elements, the dark gray block area is mainly enriched in Cr elements, the light gray area is mainly composed of Ni, Cr and W elements, and the white area is mainly enriched in Bi elements. Fig.10 The XRD diffraction pattern analysis of the composite material surface shows that the black phase in the composite material is mainly composed of Cr 2 O 3 The dark gray block phase is mainly a solid solution rich in Cr, the light gray phase is a NiCrW solid solution, and the white phase is mainly composed of NiBi and NiBi 3 Composition. Through analysis, it can be found that Bi as an additive 2 O 3 It was not detected, but NiBi and NiBi were detected 3 Therefore, it can be further inferred that during the hot pressing sintering process, Bi 2 O 3 Under high temperature and high pressure, it decomposes and reacts with Ni and Cr to form Cr 2 O 3 , NiBi and NiBi 3 Waiting for new phases, and Fig.10 The XRD analysis results of the composite surface are consistent.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A NiCrW alloy-based composite material for high-temperature alloy moving parts, characterized in that: Including the following raw materials in percentage by weight: Ni 66.50~69.30%, Cr 19.0~19.80%, W 9.50~9.90%, Bi2O31.0~5.0%.

2. The NiCrW alloy-based composite material for high-temperature alloy kinematic parts according to claim 1, characterized in that: Ni67~68.25%, Cr 19.2~19.6%, W 9.60~9.80%, Bi2O32~4%.

3. The method for preparing the NiCrW alloy-based composite material for high-temperature alloy moving parts according to claim 1 or 2, characterized in that: The following steps are involved: According to the component proportion of the NiCrW alloy-based composite material for high-temperature alloy kinematic parts, Ni powder, Cr powder, W powder and Bi2O3 are mixed and mechanically alloyed to obtain a mixed powder; The mixed powder is pressed and hot-pressed and sintered in sequence to obtain a NiCrW alloy-based composite material for high-temperature alloy moving parts.

4. The preparation method according to claim 3, characterized in that: The particle sizes of the Ni powder, Cr powder, W powder and Bi2O3 are independently ≤100 μm, and the purities are independently >99.0%.

5. The preparation method according to claim 3 or 4, characterized in that: The mechanical alloying method is wet ball milling; the wet ball milling time is 20 to 30 hours, the rotation speed is 200 to 400 r / min, and the ball-to-material mass ratio is 5 to 10:

1.

6. The preparation method according to claim 3, characterized in that: The pressing pressure is ≤10MPa.

7. The preparation method according to claim 3, characterized in that: The dynamic vacuum degree of hot pressing sintering is less than 1.0×10 -2 Pa.

8. The preparation method according to claim 1 or 7, characterized in that: The hot pressing sintering temperature is 1150-1250° C., the pressure is 25-30 MPa, and the heat preservation and pressure holding time is 30-90 minutes.

9. Use of the NiCrW alloy-based composite material for high-temperature alloy moving parts according to claim 1 or 2 or the NiCrW alloy-based composite material for high-temperature alloy moving parts prepared by the preparation method according to any one of claims 3 to 8 in aircraft engine turbine rotating mechanisms and self-lubricating bearing components.